LEADERSHIP STYLE AND INDUSTRIAL RELATIONS MEANS AS DETERMINANTS OF A FIRM'S PERFORMANCE MEDIATED BY INDUSTRIAL RELATIONS CLIMATE - M Faisal (Institut Teknologi Sains Bandung, 2024)
Globally, companies have faced conflict in the workplace, which has had an unfavorable impact on organizational performance. The adverse effects on the Company can include loss of revenue, company assets, and even loss of people's lives (Waweru, 2021).Leadership plays a vital role in ensuring that every resource allocation has a positive link to the organizational objectives. However, Jha and Singh (2019) addressed the relationship between leadership roles and the industrial relations ( I.R.) climate. The study's design is descriptive and quantitative. It used structured questionnaires as its instrument. Participants were from various organizational stakeholders. The number of samples was calculated based on an unknown population; therefore, the minimum sample required is 387. This study used convenience sampling and the snowball sampling method. This study showed that transformational Leadership and I.R. instruments positively influence I.R. climate. However, I.R. instruments have a more significant impact on I.R. climate. This is because I.R. instruments are about actual implementation, which everyone can witness. This study also confirmed that I.R. climate positively links to organizational performance. This study has several limitations. First, there were only two internal factors. Other internal factors, such as the H.R. process, internal communication, and organizational culture, can be recommended for future research